IT-DASHBOARD APPLICATION TO DETERMINE THE TYPE OF SUBSIDIZED ASSISTANCE - Renita Astri; Zulfahmi Zulfahmi; Zulfahmi -; Ahmad Kamal (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
IT-Dashboard is a user interface that shows information that can be read easily by users. The IT-Dashboar application of the subsidized assistance type decision support system was built to help and facilitate the community to find information on the type of subsidized assistance, as well as to help sub-district officials to determine which residents are eligible to receive assistance according to the criteria set by the central government so that assistance can be distributed on target. The case study will be conducted on poor families in the Lubuk Begalung sub-district of Padang city. This decision support system uses the AHP (Analytical Hierarchy Process) method to determine the type of subsidy for poor families. The AHP method is basically a comprehensive decision-making model by considering qualitative and quantitative aspects. The AHP method was chosen because it is conceptually simple, easy to understand, computationally efficient, and can measure the relative performance of decision-making alternatives. Keywords: Assistance, Subsidized, Support, Decision, Poor